Caribbean transnationalism as a gendered process. - Ho, Christine G.T. (1999)
Locates gender within capitalist relations of production by examining the role of Caribbean women as workers and mothers and as key players in the construction and maintenance of social relationships that cross national boundaries. Demonstrates how Caribbean family units are constantly being reshaped by the changing needs of global capitalism. Identifies the tremendous human costs entailed in transnationalism. Makes explicit the relation to transnationalism of global capitalism and the implications of transnationalism for class reproduction and differentiation.